2016
DOI: 10.1007/s00033-016-0644-0
|View full text |Cite
|
Sign up to set email alerts
|

Global dynamics of delay recruitment models with maximized lifespan

Abstract: Abstract. We study the dynamics of the differential equationwith two delayed terms, representing a positive and a negative feedback. We prove delay-dependent and absolute global stability results for the trivial and for the positive equilibrium. Our theorems provide new mathematical results as well as novel insights for several biological systems, including three-stage populations, neural models with inhibitory and excitatory loops, and the blood platelet model of Bélair and Mackey. We show that, somewhat surp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In the context of a disease called "cyclic thrombocytopenia" [11], Bélair et al [2] found that in the case where the function g has a bell-shape given by g(x) := f 0 θ n x θ n +x n , increasing the death rate γ induces a de-stabilization of the positive equilibrium. Equation (1.1) with the same function g has also been studied by El-Morshedy et al [10] as authors identified conditions for the global stability of either the trivial equilibrium or the positive equilibrium.…”
Section: Loïs Boullu Laurent Pujo-menjouet and Jacques Bélairmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of a disease called "cyclic thrombocytopenia" [11], Bélair et al [2] found that in the case where the function g has a bell-shape given by g(x) := f 0 θ n x θ n +x n , increasing the death rate γ induces a de-stabilization of the positive equilibrium. Equation (1.1) with the same function g has also been studied by El-Morshedy et al [10] as authors identified conditions for the global stability of either the trivial equilibrium or the positive equilibrium.…”
Section: Loïs Boullu Laurent Pujo-menjouet and Jacques Bélairmentioning
confidence: 99%
“…The derivation of this equation from the structured PDEs describing the two populations can be found in [10]. The immature cells are megakaryocytes, whose production rate is a decreasing function of the platelet count, and which release between 1000 and 3000 platelets after a maturation time τ 1 .…”
Section: Loïs Boullu Laurent Pujo-menjouet and Jacques Bélairmentioning
confidence: 99%
“…where ρ 1 and ρ 2 are the survival probabilities for the two different classes [14]; and a, b : [0, +∞) → (0, +∞) are continuous and bounded functions. The reader can consult [1,12,[14][15][16][17][18] for other delay differential equations with multiple delays coming from real problems. Although its importance is well recognized, seasonality is frequently neglected in mathematical models.…”
Section: Introductionmentioning
confidence: 99%